If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 35 = 4x + 35 Reorder the terms: 35 + 3x = 4x + 35 Reorder the terms: 35 + 3x = 35 + 4x Add '-35' to each side of the equation. 35 + -35 + 3x = 35 + -35 + 4x Combine like terms: 35 + -35 = 0 0 + 3x = 35 + -35 + 4x 3x = 35 + -35 + 4x Combine like terms: 35 + -35 = 0 3x = 0 + 4x 3x = 4x Solving 3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = 4x + -4x Combine like terms: 3x + -4x = -1x -1x = 4x + -4x Combine like terms: 4x + -4x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| (5x-4)/3-5(7+6x)/8=7 | | 32-4x=2x | | 32-4x=7x | | 32-4x=6x | | 2X+5=13+4X | | a/8=13 | | 32-4x=6x+22 | | n-11=25 | | 2w+8x-11y+7w+4x+4y= | | 9x+6=3x-12 | | n/4+10 | | h-5=3*7 | | n-5=19 | | n+33=52 | | 6x-2x=12-4 | | 211-5x=40x+21 | | 5-10x=59-31x | | ln*5*X=3 | | 21/7+87/9(4+9) | | y(y+2)=3 | | 2(y-1)=4x+5 | | 4x=10x-24 | | 2(7b-1)33=19b | | 48-6x=21x+15 | | -4-7q+2q^2=0 | | -44-2x=10x-8x | | 7z+2-3z+5=15 | | F(14)=3(14)+2 | | (2x-5)/9-8(x+3)/3+4=5 | | 3-3x+4x-6=5x+1-x | | 8x-3=5(7-x) | | 6x+6=18-6x |